2022
DOI: 10.3390/app12020876
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of a Demineralized Bone Matrix: An In Vitro Pilot Study

Abstract: Demineralized bone matrix (DBM) is commonly used for the reconstruction of bone defects. Early graft consolidation involves a transient inflammatory process. It is, however, unclear whether DBM can modulate this process. To test this possibility, we prepared acid lysates of demineralized ground cortical (DGC) and moldable demineralized fibers (MDF). Murine RAW 264.7 and primary bone marrow macrophages were exposed to acid lysates of DGC and MFD prior to provoking an inflammatory response with lipopolysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A previous study examined the inflammatory reaction caused by three different commercially available demineralized matrices (DBM) using a murine air pouch model, highlighting the importance of considering both efficacy and safety of materials and methods used for their processing when selecting a bone grafting method [ 41 ]. At the same time demineralized bone matrix (DBM) generated by yet another method exhibited a lower inflammation-induced expression of inflammatory mediators in murine cell-based bioassays [ 42 ]. However, current understanding allows modification of biomaterial physico-chemical design to support biomaterial-induced macrophage polarization for tissue regeneration [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study examined the inflammatory reaction caused by three different commercially available demineralized matrices (DBM) using a murine air pouch model, highlighting the importance of considering both efficacy and safety of materials and methods used for their processing when selecting a bone grafting method [ 41 ]. At the same time demineralized bone matrix (DBM) generated by yet another method exhibited a lower inflammation-induced expression of inflammatory mediators in murine cell-based bioassays [ 42 ]. However, current understanding allows modification of biomaterial physico-chemical design to support biomaterial-induced macrophage polarization for tissue regeneration [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, current understanding allows modification of biomaterial physico-chemical design to support biomaterial-induced macrophage polarization for tissue regeneration [ 43 ]. In an in vitro pilot study by Panahipour et al ., it was found that DBM demonstrated anti-inflammatory activity by reducing the expression of IL-1β and IL-6 in RAW 264.7 macrophage cells, suggesting a potential modulation of the inflammatory responses [ 42 ]. Such conflicting results may be attributed to differences in the methodology of the studies, particularly in terms of the graft processing techniques utilized, which produced variable physico-chemical and topographical characteristics that elicit varying host tissue responses besides the likely presence of residual native cells within the grafts that may evoke the inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%